Improving Students Mathematical Understanding by Using Discovery Learning Models for Senior High School Students in Kampar District - Imayati Imayati; Kartini Kartini; Zulkarnain Zulkarnain (Journal of Educational Sciences, 2020)
Mathematical understanding is a very important ability possessed by students in solving mathematical problems. The purpose of this study is to find out the improvement in students mathematical understanding using discovery learning models. This research was a quasi-experimental study with a non equivalent control group design. The samples in this study were SMAN 1 Bangkinang, SMAN 1 XIII Koto Kampar and SMAN 2 Koto Kampar Hulu taken by purposive sampling technique. The data analysis technique used was the t test, and the Mann-Whitney U test. The results showed an increase in mathematical understanding of students learning using discovery learning models is better than students learning to use conventional learning models at the top level of school, medium and as a whole, but at the lower level schools have not increased.